The impact of advancing mine liquidation processes on the ability to reopen previously abandoned deposits - Marek Pieszczek; Janusz Smoliło; Małgorzata Wysocka; Andrzej Chmiela; Małgorzata Magdziarczyk; Adam Smoliński (International Journal of Coal Science & Technology)
Abstract Changing political and market conditions have disrupted energy security. European economies are planning to utilize their own resources of energy raw materials, including consideration of the advisability of returning abandoned coal resources to use. The research using the proposed methodology examined the impact of the ongoing mine closure processes on the potential ability to develop the remaining deposit. It was found that the greatest influence on the availability of unclosed shafts was the active concession to extract minerals from the deposit and the availability of unclosed main plant facilities. The assessment of the possibilities of coal resources management in the deposits of liquidated mines has not been the subject of extensive scientific research so far. The information obtained can be used as a reference point for detailed analysis and multi-criteria evaluation, after which the decision maker makes the decision. The method is designed for liquidated mines, but with certain modifications it can also be used by mining companies.